Information technologies as factor of forming of national competitiveness of countries - Перепелица, Анна (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism)
The article «Information technologies as factor of forming of national competitiveness of countries» deals with orming of competitiveness of countries features and rates of development of information technologies, and also prospects of development and examples of informative NT, are considered in a world economy». Considered change of structure of factors of forming of competitiveness of countries in a world economy, increase of value of information technologies, connection is analyzed between the height of high–tech and in particular information technologies and by the level of competitiveness. Levels and factors of competitiveness of information technologies are also considered. Information technologies as constituents of processes of the use of informative resources are examined societies that to present tense passed the great number of the evolutional stages. The article analyzes the competitiveness of some European countries, due to introduction of information technologies. Also, in the article, becoming of theory of informative economy and influence of modern information technologies is examined on different parties of socio–economic life. The special attention is spared to the fundamental changes in behavior of basic economic subjects (consumers, firms, state) under act of NT and on the feature of realization in the new terms of public economic policy.